2015
DOI: 10.1097/01.j.pain.0000460345.92588.4b
|View full text |Cite
|
Sign up to set email alerts
|

Lipid kinases as therapeutic targets for chronic pain

Abstract: Existing analgesics are not efficacious in treating all patients with chronic pain and have harmful side effects when used long-term. A deeper understanding of pain signaling and sensitization could lead to the development of more efficacious analgesics. Nociceptor sensitization occurs under conditions of inflammation and nerve injury where diverse chemicals are released and signal through receptors to reduce the activation threshold of ion channels, leading to an overall increase in neuronal excitability [98;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 108 publications
(152 reference statements)
0
9
0
Order By: Relevance
“…For instance, AMPK is a core regulator of phospholipid biosynthesis and metabolism, but this aspect of AMPK function has been almost entirely ignored in the context of neuronal excitability. This area of investigation offers great opportunity for new discovery because it is well known that lipids are key regulators of channel, G-protein coupled receptor, and kinase function in nociceptors (Piomelli et al 2014; Loo et al 2015) and other neurons. Here, we propose that basic cell biology studies on the role of AMPK in neuronal excitability can greatly enhance our understanding of the target and how it can be manipulated to achieve effects that are relevant for pain therapeutics.…”
Section: 10 What Do We Know (And More Importantly Not Know) Aboumentioning
confidence: 99%
“…For instance, AMPK is a core regulator of phospholipid biosynthesis and metabolism, but this aspect of AMPK function has been almost entirely ignored in the context of neuronal excitability. This area of investigation offers great opportunity for new discovery because it is well known that lipids are key regulators of channel, G-protein coupled receptor, and kinase function in nociceptors (Piomelli et al 2014; Loo et al 2015) and other neurons. Here, we propose that basic cell biology studies on the role of AMPK in neuronal excitability can greatly enhance our understanding of the target and how it can be manipulated to achieve effects that are relevant for pain therapeutics.…”
Section: 10 What Do We Know (And More Importantly Not Know) Aboumentioning
confidence: 99%
“…Phosphatidylinositol 4,5-bisphosphate, also known as PI(4,5)P 2 or PIP 2 , has important roles in cell signaling and is immediately downstream of many pronociceptive signaling pathways, despite only accounting for 0.5% to 1% of the phospholipid molecules in cells. 6 , 7 Type 1 phosphotidylinositol 4-phosphate 5-kinases (PIP5KIs) synthesize PIP 2 by phosphorylating the large pools of phosphatidylinositol 4-phosphate in cells. There are three Pip5k1 genes, two of which are ubiquitously expressed ( Pip5k1a and Pip5k1b ), while the third (phosphatidylinositol 4-phosphate 5-kinase type 1 gamma, Pip5k1c ) is expressed predominantly in neuronal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…There are three Pip5k1 genes, two of which are ubiquitously expressed ( Pip5k1a and Pip5k1b ), while the third (phosphatidylinositol 4-phosphate 5-kinase type 1 gamma, Pip5k1c ) is expressed predominantly in neuronal tissues. 6 , 8 , 9 We previously found that global heterozygous deletion of Pip5k1c reduced PIP 2 in dorsal root ganglia (DRG) and reduced pain signaling and inflammatory sensitization. 10 While these studies suggested that it might be possible to reduce pronociceptive signaling by selectively inhibiting a lipid kinase that generates PIP 2 in DRG neurons, whether the decrease observed in pain behavior was due to a reduction in the enzyme expression specifically in sensory neurons or globally throughout the nervous system was unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Acting as a multifunctional molecule, PIP 2 plays pivotal roles in normal and pathological cellular functions 18 19 20 . For instance, PIP 2 is implicated in cell proliferation and neurological diseases 21 22 23 . Consequently, the lipid kinases including phosphatidylinositol 4-kinases (PI4Ks) and phosphatidylinositol-4-phosphate 5-kinases (PIP5KIs) responsible for PIP 2 synthesis are considered to be potential therapeutic targets for various disorders involving altered neuronal excitability such as chronic pain 19 22 24 25 26 .…”
mentioning
confidence: 99%
“…For instance, PIP 2 is implicated in cell proliferation and neurological diseases 21 22 23 . Consequently, the lipid kinases including phosphatidylinositol 4-kinases (PI4Ks) and phosphatidylinositol-4-phosphate 5-kinases (PIP5KIs) responsible for PIP 2 synthesis are considered to be potential therapeutic targets for various disorders involving altered neuronal excitability such as chronic pain 19 22 24 25 26 . In addition, the degradation of PIP 2 is subject to dynamic regulation by many important neuronal transmitters via G protein-coupled receptor (GPCR)-induced phospholipase C (PLC) activation, which in turn affects many important downstream targets including a wide array of ion channels 19 27 28 .…”
mentioning
confidence: 99%